ENGLISH TEACHERS’ MASTERY OF THE ENGLISH ASPIRATION AND STRESS RULES - Arina Isti'anah (PAROLE: Journal of Linguistics and Education, 2013)
This  paper  tries  to  observe  the  English  teachers’  awareness  and representation  of  the  English  aspiration  and  stress  rules.  The research purposes to find out whether or not the teachers are aware of the English aspiration and stress rules,  and to find out how the teachers represent the English aspiration and stress rules. Based on the analysis, it can be concluded that the teachers’ awareness of the English aspiration and stress rules is very low. It is indicated with the percentage which equals to 44% and 48% for English aspiration and  stress  rules.  In  representing  the  English  aspiration  and  stress rules, the teachers face the problems in producing aspiration in the pronunciation,  placing  the  right  stress  and  pronouncing  three  and four  X  in  the  coda  position.  There  are  two  reasons  affecting  the teachers’  awareness  of  the  English  aspiration  and  stress  rules namely exposure and L1 influence. Artikel  ini  bertujuan  untuk  meneliti  kesadaran  dan  representasi aturan aspirasi dan tekanan oleh guru bahasa Inggris. Penelitian ini bertujuan  untuk  menjelaskan  apakah  guru  bahasa  Inggris mempunyai  kesadaran  atas  aturan  aspirasi  dan  tekanan  dalam bahasa  Inggris,  dan    untuk  menunjukkan  bagaimana  guru  Bahasa Inggris  mewujudkan  aturan  aspirasi  dan  tekanan  dalam  pelafalan mereka.  Berdasarkan  analisis  yang  dilakukan,  dapat  disimpulkan bahwa  kesadaran  guru  Bahasa  Inggris  atas  aturan  aspirasi  dan tekanan  dalam  Bahasa  Inggris  masih  sangat  rendah.  Hal  tersebut ditunjukkan  oleh  rendahnya  prosentase  dalam  perwujudan  aturan aspirasi  dan  tekanan:  44%  dan  48%.  Dalam  mewujudkan  aturan aspirasi dan tekanan, guru Bahasa Inggris menemui masalah dalam menghasilkan  aspirasi  dalam  pelafalan,  meletakkan  tekanan  pada suku  kata  yang  tepat  dan  pada  posisi  X  yang  berada  pada  posisi ketiga  atau  keempat.  Terdapat  dua  alasan  yang  memengaruhi kesadaran partisipan atas aturan aspirasi dan tekanan, yaitu pajanan dan pengaruh bahasa pertama.